Artistic Novelties or Political Tools? Circulating Cold War Art Exhibitions in Finland. - Koskinen Maija (Purdue Scholarly Publishing Services, 2025)
The cultural Cold War was a global phenomenon, but how was it fought in Finland, on the periphery of Northern Europe? The essay brings a previously insufficiently known Finnish perspective into the study of the cultural Cold War by introducing a research project, Mission Finland – Cold War Cultural Diplomacy at the crossroads of East and West, 1945–1991. The essay discusses study methods of international art exhibitions as soft power and introduces – with concrete Finnish examples – the concept of “state-run exhibition” as a means to comprehend the role of circulating art exhibitions as Cold War cultural diplomacy.